Samuel Phillips Lee papers - Lee, Samuel Phillips, 1812-1897.
Correspondence, memoranda, logbook abstracts, reports, lists, requisition orders, printed matter, and other papers relating to the naval activities of the Union forces in the Civil War. Pertains chiefly to Lee's service commanding the North Atlantic Blockading Squadron (1862-1864) and the Mississippi Squadron (1864-1865). Subjects include the Union blockade, Confederate and Northern blockade runners, the command of Benjamin F. Butler in and around the Newport News, Virginia, area; and the Mississippi River campaign. Includes a logbook for the USS Mississippi (Paddle frigate) in the summer of 1861. Correspondents include James B. Devoe, John G. Foster, Gideon Welles, and the U.S. Navy Dept.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Butler, Benjamin F. -- 1818-1893.; Devoe, James B. -- Correspondence; Foster, John G. -- 1823-1874 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; United States. -- Navy Department -- Correspondence; United States. -- Navy. -- Mississippi Squadron; United States. -- Navy. -- North Atlantic Blockading Squadron (1861-1865); Mississippi (Paddle frigate); Mississippi River Valley -- History -- Civil War, 1861-1865 -- Campaigns; Newport News (Va.) -- History; United States -- History -- Civil War, 1861-1865 -- Blockades; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Naval officers